Effects of manidipine vs. amlodipine on intrarenal haemodynamics in patients with arterial hypertension. (14th December 2012) - Ott, Christian; Schneider, Markus P.; Raff, Ulrike; Ritt, Martin; Striepe, Kristina; Alberici, Marco; Schmieder, Roland E.
<x xml:space="preserve">Abstract</x> WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT Dihydropyridine calcium channel blockers (CCBs) are widely used antihypertensive drugs. Evidence from animal studies indicates there are differences between CCBs in their renal haemodynamic effects suggesting that manidipine reduces, whereas amlodipine increases intraglomerular pressure but data from humans are scarce. WHAT THIS STUDY ADDS In this study amlodipine was found to increase significantly intraglomerular pressure whereas manidipine decreased intraglomerular pressure in people with essential hypertension. This difference was attributed to significant vasodilation of the afferent arteriole with amlodipine compared with manidipine. This study for the first time has confirmed in humans data from experimental models on the different action of CCBs on dilatory capacity on efferent and afferent arterioles. AIMS Intraglomerular pressure is one of the main drivers of progression of renal failure. Experimental data suggest that there are important differences between calcium channel blockers (CCBs) in their renal haemodynamic effects: manidipine reduces, whereas amlodipine increases intraglomerular pressure. The aim of this study was to investigate the effects of manidipine and amlodipine treatment on intragomerular pressure (Pglom) in patients with mild to moderate essential hypertension. METHODS In this randomized, double‐blind, parallel group study, hypertensive patients were randomly assigned to receive manidipine 20 mg (n= 54) or amlodipine 10 mg (n= 50) for 4 weeks. Renal plasma flow (RPF) and glomerular filtration rate (GFR) were determined by constant‐infusion input‐clearance technique with p‐aminohippurate (PAH) and inulin. Pglom and resistances of the afferent (RA) and efferent (RE) arterioles were calculated according to the model established by Gomez. RESULTS Pglom did not change in the manidipine group (P= 0.951), whereas a significant increase occurred in the amlodipine group (P= 0.009). There was a significant difference in the change of Pglom by 1.2 mmHg between the manidipine and amlodipine group (P= 0.042). In both treatment arms, RA was reduced (manidipine P= 0.018; amlodipine P < 0.001). The reduction of RA was significantly more pronounced with amlodipine compared with manidipine treatment (P < 0.001). RE increased in both treatment arms (manidipine P= 0.012; amlodipine P= 0.002), with no difference between the treatment arms. Both CCBs significantly reduced systolic and diastolic blood pressure (BP) (both P < 0.001). However, amlodipine treatment resulted in a significantly greater decrease of BP compared with manidipine (P < 0.001). CONCLUSIONS In accordance with experimental data after antihypertensive treatment of 4 weeks, intraglomerular pressure was significantly lower with the CCB manidipine than with amlodipine, resulting and explaining their disparate effects on albuminuria.